Lithium-containing metal strip surface leveling and artificial SEI coating synchronous treatment process, modified lithium-containing metal strip and application of modified lithium-containing metal strip
Through the synchronous treatment process of lithium metal belt surface flattening and artificial SEI coating, the problems of low structural strength and active chemical properties of lithium metal negative electrode materials during processing and application are solved, and efficient and low-cost electrochemical stability and performance improvement are achieved.
Patent Information
- Application Number
- CN202411512874.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-10-28
AI Technical Summary
During the processing and application of existing lithium metal negative electrode materials, there are problems such as low structural strength, deformation stress caused by electrochemical reactions, and active chemical properties, resulting in deterioration of performance and high production costs.
The surface flattening and artificial SEI coating of lithium-containing metal strips are synchronized by pre-coating the film-forming sacrificial agent and using rolling processing stress to achieve the flattening of the lithium-metal surface and the continuous and uniform coating of artificial SEI.
The surface flatness of lithium metal negative electrode materials and the integrity of artificial SEI are achieved, the electrochemical stability is improved, the dendrite problem is reduced, and the production cost and energy consumption are reduced.
Smart Images

Figure CN119897353A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical energy storage materials, and in particular to a simultaneous treatment process for surface flattening and artificial SEI coating of a lithium-containing metal strip, a modified lithium-containing metal strip, and application of the modified lithium-containing metal strip as a negative electrode material in a lithium metal primary / secondary battery. Background Art
[0002] Currently, the widely used commercial lithium-ion batteries based on graphite negative electrodes are limited by the low capacity density of graphite materials (372mAh / g) and cannot meet the future social demand for high energy density energy storage devices (400-500Wh / kg). In order to develop a battery system with higher energy density, the core work is to develop negative electrode materials with low electrode potential and high capacity density.
[0003] Among all the alternative materials, lithium metal negative electrode materials have the lowest electrode potential (-3.04V vs. SHE) and extremely high mass specific capacity (3860mAh / g), and can match positive electrode materials such as sulfur and air to achieve a high energy density battery system with an energy density of more than 600Wh / kg, showing great application prospects. Therefore, it has received widespread attention from scientific research and industry, and is also one of the main directions of current high energy density battery research and development.
[0004] However, the practical application of lithium metal anode faces several challenges: First, the mechanical properties of lithium metal foil are relatively low, with an ultimate tensile strength of only 1.5Mpa and a Young's modulus of only 4.9Gpa. Therefore, during the processing of lithium metal foil negative electrode, battery assembly and application, structural damage is very likely to occur; Secondly, the electrochemical reaction of the lithium metal negative electrode is accompanied by unrestricted deposition / dissolution of lithium metal and severe deformation stress, which leads to cracking and pulverization of the metal foil, and is accompanied by continuous irreversible reaction between the active lithium metal and the electrolyte, resulting in loss of battery active materials and performance degradation; Finally, due to its active chemical properties, metallic lithium or lithium metal-based composite materials will quickly undergo side reactions and deteriorate in a humid atmosphere, and lithium metal melts are also very easy to oxidize in a dry atmosphere. Therefore, when using lithium metal / alloy foil as a negative electrode for a battery, vacuum or inert atmosphere protection is required, which greatly increases the production cost.
[0005] To address the problems of low structural strength and active chemical properties of lithium metal, the most commonly used method in the industry is to compound metallic lithium with other high-strength conductive film materials (such as copper foil, porous carbon felt, etc.) or form alloys during the preparation of negative electrode materials, thereby preparing lithium-containing metal strips and using the high-strength composite phase in the metal strips to enhance the overall structure of the metal negative electrode, thereby avoiding damage to the negative electrode structure caused by stress during processing and application; and coating the lithium metal side of the lithium-containing metal strip with an artificial SEI film composed of a continuous inorganic or organic solid electrolyte, thereby passivating the metal surface to a certain extent and improving the stability of lithium metal in environments such as air and liquid electrolytes.
[0006] However, the current process also has two disadvantages in actual production and application: First, the current cold rolling process of lithium-containing metal strips is a non-lubricated cold rolling process. During the rolling process, it is difficult to maintain the stability of the lithium metal dead zone. The internal and external friction of the lithium-containing metal strip surface is large and the deformation stress distribution is uneven, resulting in serious defects such as embossing, bite marks, and scratches on the lower-strength lithium metal side, which damages the surface flatness of the lithium metal. When the lithium-containing metal strip is subsequently used as a negative electrode in a battery, factors such as the many surface defects, poor flatness, and uneven distribution of residual stress from surface work hardening of the metal strip will induce uneven deposition of lithium metal, seriously damaging the uniformity and stability of the negative electrode surface interface, causing the destruction of the surface interface passivation layer and the proliferation of dendrites, accelerating the failure of the negative electrode.
[0007] Secondly, the current artificial SEI modification process for the surface of lithium-containing metal strips in the industry is too complicated and cumbersome: first, the lithium-containing metal strip is formed by cold rolling, then the oxides and other impurities on the surface of the metal strip are removed, and finally the surface of the lithium-copper composite strip is coated with a film-forming sacrificial agent combined with an electrochemical / heat treatment formation scheme, a vacuum sputtering coating process, and a coating of a polymer solid electrolyte membrane to form an artificial SEI coating on the lithium metal surface of the lithium-containing metal strip. Since the forming process and the surface modification process of the lithium-containing metal strip are carried out separately, the production steps are significantly complicated, and the demand for production equipment, special process environment, and energy consumption has also increased, resulting in a significant increase in the production cost of the artificial SEI-modified metal strip and a decrease in yield. In addition, due to the limitations of the film-forming mechanism, the uniformity, continuity, and integrity of the artificial SEI coated on the surface of the lithium-containing metal strip by the existing process are not ideal, so the passivation and protection of the lithium-containing metal strip is not reliable enough.
[0008] In summary, in order to realize a low-cost, high-energy-density lithium metal battery system, there is an urgent need for a solution that can quickly, continuously, low-cost, and low-energy prepare lithium-containing metal strips with smooth surfaces and defect-free surfaces, and a complete, continuous, and uniform artificial SEI coated on the lithium metal side. Summary of the invention
[0009] In view of the problems in the current industry that the drying and cold rolling forming steps and the artificial SEI step of lithium-containing metal strips are separated, the modification process is cumbersome and the product quality is poor, the present invention proposes a solution for simultaneously performing surface flattening and artificial SEI modification of the lithium-containing metal strip, so as to obtain a lithium-containing metal strip with a flat and defect-free lithium metal side and a lithium metal surface coated with a complete and uniform artificial SEI. When it is used as the negative electrode material of a lithium metal battery, a dendrite-free negative electrode with long-term stable charging and discharging can be achieved.
[0010] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is: In the first aspect of the present invention, a process for simultaneous surface flattening and artificial SEI coating of a lithium-containing metal strip is provided, comprising the following steps: S1, pre-coating a film-forming sacrificial agent on the lithium metal surface of the lithium metal strip to form a liquid film; S2: using a flat and smooth metal roller to roll the lithium metal surface of the lithium metal strip, thereby simultaneously achieving lithium metal surface flattening and surface artificial SEI coating; The film-forming sacrificial agent serves as both a rolling lubricant and a sacrificial agent precursor required for the formation of an artificial SEI to react with lithium metal to form an artificial SEI film.
[0011] Preferably, the film-forming sacrificial agent is selected from at least one of the following substances: liquid halogenated hydrocarbons and their derivatives, solutions of inorganic salts, and solutions of sulfided organic small molecules.
[0012] Preferably, the liquid halogenated hydrocarbons and their derivatives are one or more of halogenated alkanes such as 1,2-dibromoethane, trichloroethylene, hexafluorobenzene, pentafluorobromobenzene, olefins, benzene-based organic small molecules and their derivatives, the inorganic salt is at least one of nitrates and phosphates (the metal ions of the nitrates and phosphates referred to include but are not limited to silver, zinc, aluminum, tin, germanium, gallium, indium, niobium, antimony, bismuth, molybdenum, etc.), the sulfide organic small molecules include organic small molecules and inorganic salts, wherein the organic small molecules include DtbDS, DPDSe, DPDTe, DMDS, DMTS, AMDS, BTB, ADS and other sulfide or thiobenzene-based small molecules and their derivative small molecules, and the inorganic salts include one or more sulfides or polysulfides of metals such as lithium, silver, zinc, aluminum, tin, germanium, gallium, indium, niobium, antimony, bismuth, molybdenum, etc.
[0013] Preferably, the lithium-containing metal belt is selected from any one of a pure lithium metal belt, a binary or multinary alloy belt of lithium and any other metal, a lithium-copper composite belt, and a lithium-carbon composite belt.
[0014] Preferably, metallic lithium or lithium alloy is distributed on at least one side of the metal strip, and the lithium-containing metal strip has a thickness of 1 to 100 μm and a lithium content of 1 to 100%.
[0015] Preferably, the thickness of the liquid film formed in step S1 is 10-100 μm.
[0016] Preferably, in step S2, the process conditions for rolling are: processing stress is 1~100Mpa, single rolling reduction is 0.01~1mm, roller linear speed is 0.1~100 cm / s, the processing process is a combination of rough rolling and finish rolling, and the rolling passes are 2~10 times.
[0017] Preferably, the lithium-containing metal strip surface flattening and artificial SEI coating simultaneous treatment process comprises the following steps: S1, pre-coating 1,2-dibromoethane as a film-forming sacrificial agent on the lithium metal surface of the lithium-copper composite strip to form a liquid film; S2: Use a flat and smooth metal roller to roll the lithium metal surface of the lithium metal strip, and simultaneously achieve lithium metal surface flattening and surface artificial SEI coating. The rolling process conditions are: The relative humidity of the processing environment is 5~10%, the rolling passes are 2~5 times, the rolling process is 2H rough rolling followed by 4H finishing rolling, the single reduction of rough rolling is 1~10μm, the single reduction of finishing rolling is 0.1~2μm, the roll winding speed is 1~30 cm / s, and the relative humidity of the rolling processing environment is 5~10%.
[0018] The second aspect of the present invention provides a modified lithium-containing metal strip, which is prepared by the method as described above.
[0019] A third aspect of the present invention provides a use of the modified lithium-containing metal strip as described above as a negative electrode material in a lithium metal primary / secondary battery.
[0020] The beneficial effects of the present invention are: (1) The present invention provides a simultaneous treatment process for surface flattening and artificial SEI coating of a lithium-containing metal strip, a modified lithium-containing metal strip, and the use of the modified lithium-containing metal strip as a negative electrode material in lithium metal primary / secondary batteries; the present invention utilizes the multiple characteristics of common film-forming sacrificial agents to propose a method for simultaneously achieving surface flattening and artificial SEI modification of the lithium metal side of a lithium-containing metal strip in a single processing step, which can improve the surface quality of the lithium metal of the lithium-containing metal strip raw material and form a continuous, complete, uniform, and dense artificial SEI on the lithium metal surface in a short period of time. Through this process design, the problems of poor lithium metal surface quality, poor uniformity and integrity of the modified layer, and reduced yield and increased cost caused by distributed processing in the preparation and modification of traditional lithium-containing metal strips can be avoided. Through the process proposed by the present invention, large-scale preparation of lithium-containing metal strips with flat surfaces and artificial SEI coating can be achieved through simple procedures, and the product quality is high and the consistency is good, so it is more suitable for the production of commercial battery electrode materials and helps to improve the performance consistency of commercial battery cells.
[0021] (2) The process of the present invention adopts a lubricated cold rolling process during the processing of the lithium-containing metal strip. The processing stress during the rolling process is evenly dispersed, so that the lithium metal side of the lithium-containing metal strip can be evenly deformed, thereby improving the metal surface flatness, reducing defects and achieving uniform residual stress dispersion; in addition, the uniform processing stress can induce a uniform film-forming reaction between the metal lithium surface and the film-forming sacrificial agent in a large area, thereby forming a continuous, uniform, complete and dense artificial SEI dominated by inorganic lithium salts with high ion conductivity and high strength on the lithium metal surface.
[0022] (3) When the lithium-containing metal strip prepared by the process of the present invention is used as the negative electrode of a lithium metal battery, the flat, defect-free lithium metal substrate with uniformly dispersed residual stress can induce a relatively uniform lithium metal deposition / extraction reaction, and the high-strength continuous, complete, and uniform inorganic salt-dominated artificial SEI can not only improve the surface stability of the negative electrode, but also promote the uniform lithium ion mass transfer process, thereby improving the uniformity and stability of the interface reaction. Therefore, under the action of multiple structural optimizations, the electrochemical stability of the lithium-containing metal strip can be effectively improved and the dendrite problem can be alleviated.
[0023] (3) Taking the bromine-rich SEI coated lithium-copper composite strip material prepared according to the scheme of the present invention as an example, the half-cell of the lithium-copper composite strip electrode prepared according to the present invention can be used in an ester electrolyte system at 1 mA / cm 2 , 2h charge and discharge time to achieve more than 350h of stable charge and discharge while maintaining a flat negative electrode surface without dendrites. In sharp contrast, the half-cell sample based on ester electrolyte assembled by dry rolling and heat treatment of artificial SEI coated lithium-copper composite strips using existing processes showed drastic fluctuations in the voltage curve during the cycle of less than 200h, and obvious dendrites or powdering appeared on the negative electrode surface after cycling. In the subsequent full battery test, it was found that the full battery (R-LiBr / Li-Cu||LFP) of the modified lithium-copper composite belt of the present invention matched with lithium iron phosphate showed good coulombic efficiency (99.79±0.06%) and low capacity decay rate (2.52%) at 1C rate and more than 200 charge and discharge cycles, while the full battery control group (H-LiBr / Li-Cu||LFP) of the modified lithium-copper composite belt prepared by the traditional chemical formation process matched with lithium iron phosphate had low coulombic efficiency and poor stability (99.61±0.76%) during 150 charge and discharge cycles, and a high capacity decay rate (7.61%). The above two groups of control test results can prove the design superiority of the present invention in realizing the surface optimization of the lithium metal side of the lithium metal belt and artificial SEI modification by one-time processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1Schematic diagram of the process of simultaneous surface flattening and artificial SEI coating of the lithium-containing metal strip in Example 1; Figure 2 The scanning electron microscope photo and corresponding energy spectrum analysis of the lubricated cold-rolled film-forming lithium bromide artificial SEI coated lithium-copper composite strip (labeled as R-LiBr / Li-Cu) prepared in Example 1; Figure 3 Scanning electron microscope images and corresponding energy spectrum analysis of the heat-treated LiBr artificial SEI coated lithium-copper composite tape (labeled as H-LiBr / Li-Cu); Figure 4 The repeated charge and discharge voltage curve of the R-LiBr / Li-Cu half-cell prepared in Example 2; Figure 5 The repeated charge and discharge voltage curve of the H-LiBR / Li-Cu half-cell prepared in Example 2; Figure 6 The scanning electron microscope photographs of the surface morphology of the R-LiBr / Li-Cu (left) and H-LiBr / Li-Cu (right) electrodes after multiple charge and discharge cycles of the half-cell in Example 3; Figure 7 The capacity curve and coulombic efficiency curve of the R-LiBr / Li-Cu||LFP full battery experimental group and the H-LiBR / Li-Cu||LFP full battery control group in Example 4; Figure 8 The polarization voltage curves of the R-LiBr / Li-Cu||LFP full battery experimental group and the H-LiBR / Li-Cu||LFP full battery control group in Example 4; Fig. 9 Specific cycle charge and discharge voltage curves of the R-LiBr / Li-Cu||LFP full battery experimental group and the H-LiBR / Li-Cu||LFP full battery control group in Example 4. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0026] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0027] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0028] The present invention provides a simultaneous treatment process for surface flattening and artificial SEI coating of a lithium-containing metal strip, comprising the following steps: S1, pre-coating a film-forming sacrificial agent on the lithium metal surface of the lithium metal strip to form a liquid film; S2: using a flat and smooth metal roller to roll the lithium metal surface of the lithium metal strip, thereby simultaneously achieving lithium metal surface flattening and surface artificial SEI coating; Among them, the film-forming sacrificial agent acts as both a rolling lubricant and a sacrificial agent precursor required for the formation of artificial SEI to react with lithium metal to form an artificial SEI film. Through the rolling processing stress and the lubricating effect of the film-forming sacrificial agent, the surface of the lithium metal is flattened, its roughness is improved, and the residual processing stress on the surface of the lithium metal is dispersed. The formation mechanism of artificial SEI is to utilize the severe instantaneous stress and thermal effects during the rolling process to activate the uniform and instantaneous reaction between the film-forming sacrificial agent and the lithium atoms on the surface of the lithium metal in a large area, thereby forming a uniform, continuous, and complete artificial SEI with inorganic lithium salt as the main component on the surface of the lithium metal.
[0029] The selection criteria of the film-forming sacrificial agent are: having appropriate polarity and viscosity, good wettability with lithium metal / lithium alloy, being able to form a stable extreme pressure lubricating layer on the surface of lithium metal with sufficient toughness and compressive strength, being able to adjust the internal friction of lithium metal, and being able to react rapidly with lithium under external stress to form an artificial SEI. In a preferred embodiment, the film-forming sacrificial agent is selected from at least one of the following substances: liquid halogenated hydrocarbons and their derivatives, solutions of inorganic salts, and solutions of sulfided organic small molecules.
[0030] In a preferred embodiment, the liquid halogenated hydrocarbons and their derivatives are one or more halogenated alkanes, alkenes, benzene-based organic small molecules and their derivatives such as 1,2-dibromoethane, trichloroethylene, hexafluorobenzene, pentafluorobromobenzene, etc., and the inorganic salt is at least one of nitrates and phosphates (the metal ions of the nitrates and phosphates referred to include but are not limited to silver, zinc, aluminum, tin, germanium, gallium, indium, niobium, antimony, bismuth, molybdenum, etc.). The sulfide organic small molecules include organic small molecules and inorganic salts, wherein the organic small molecules include DtbDS, DPDSe, DPDTe, DMDS, DMTS, AMDS, BTB, ADS, etc. sulfide or thiobenzene-based small molecules and their derivative small molecules, and the inorganic salts include one or more sulfides or polysulfides of metals such as lithium, silver, zinc, aluminum, tin, germanium, gallium, indium, niobium, antimony, bismuth, molybdenum, etc.
[0031] In a preferred embodiment, the lithium-containing metal belt is selected from any one of a pure lithium metal belt, a binary or multinary alloy belt of lithium and any other metal, a lithium-copper composite belt, and a lithium-carbon composite belt.
[0032] In a preferred embodiment, metallic lithium or lithium alloy is distributed on at least one side of the metal strip, and the lithium-containing metal strip has a thickness of 1-100 μm and a lithium content of 1-100%.
[0033] In a preferred embodiment, the lithium-containing metal strip is the lithium-copper composite strip most commonly used in the industry, with a thickness of 50-90 μm, wherein the copper foil has a thickness of 5-10 μm.
[0034] In a preferred embodiment, the coating method in step S1 is a spray-combined scraping process, the film-forming sacrificial agent is a halogenated hydrocarbon small molecule liquid, and the thickness of the formed liquid film is 10-100 μm.
[0035] In a preferred embodiment, in step S2, the process conditions for rolling are: processing stress is 1~100Mpa, single rolling reduction is 0.01~1mm, roller linear speed is 0.1~100 cm / s, the processing process is a combination of rough rolling and finish rolling, and the rolling passes are 2~10 times.
[0036] In a preferred embodiment, the lithium-containing metal strip surface flattening and artificial SEI coating simultaneous treatment process comprises the following steps: S1, pre-coating 1,2-dibromoethane as a film-forming sacrificial agent on the lithium metal surface of the lithium-copper composite strip to form a liquid film; S2: Use a flat and smooth metal roller to roll the lithium metal surface of the lithium metal strip, and simultaneously achieve lithium metal surface flattening and surface artificial SEI coating. The rolling process conditions are: The relative humidity of the processing environment is 5~10%, the rolling passes are 2~5 times, the rolling process is 2H rough rolling followed by 4H finishing rolling, the single reduction of rough rolling is 1~10μm, the single reduction of finishing rolling is 0.1~2μm, the roll winding speed is 1~30 cm / s, and the relative humidity of the rolling processing environment is 5~10%.
[0037] The present invention also provides a modified lithium-containing metal belt, which is prepared by the method as described above.
[0038] The present invention also provides a use of the modified lithium-containing metal strip as described above as a negative electrode material in a lithium metal primary / secondary battery.
[0039] The present invention mainly utilizes the following advantages of polar artificial SEI film-forming sacrificial agents: it can not only infiltrate and spread on the surface of lithium metal to form a continuous liquid film layer with a certain strength to lubricate the rolling process, but also react with active lithium metal under the action of external energy to generate artificial SEI. Therefore, when a specific sacrificial agent is pre-coated on the lithium metal side of the lithium-containing metal strip, the sacrificial agent can infiltrate the rough lithium metal surface to form a continuous extreme pressure film. Subsequently, during the rolling, thinning and flattening process of the lithium-containing metal strip, the flat metal roller directly contacts the lithium metal side of the lithium-containing metal strip coated with the sacrificial agent and performs rolling processing, thereby triggering instantaneous high deformation stress, deformation energy and thermal effect at the contact point between the roller and the lithium metal, on the one hand, inducing a rapid and uniform artificial SEI film-forming reaction between the film-forming sacrificial agent and the lithium metal, on the other hand, utilizing the processing stress and the lubricating effect of the sacrificial agent to further flatten the lithium metal surface and form a uniform processing stress distribution, and finally, the artificial SEI structure can be compacted to reduce internal structural defects and enhance the interface bonding effect between the artificial SEI and the lithium metal.
[0040] Through the above steps and special film-forming reaction behavior, a lithium metal side with high flatness, uniform residual stress distribution and few defects can be achieved, and a high-performance artificial SEI that is dense, continuous, complete, uniform and reliably combined with lithium metal can be formed on the lithium metal surface. Since the above film-forming reaction and rolling processing behavior are carried out simultaneously, the surface optimization and artificial SEI modification of the lithium metal side of the lithium metal-containing belt can be achieved simultaneously through a one-step processing process, thereby not only obtaining a high-performance modified composite belt material, but also effectively improving the yield, reducing production costs, and reducing processing energy consumption and the need for a special production environment.
[0041] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.
[0042] Example 1 A method for simultaneously smoothing the lithium metal surface of a lithium-copper composite strip and coating it with bromine-rich artificial SEI comprises the following specific steps: A 80 μm thick lithium-copper composite strip was used as a raw material (lithium metal thickness was 70 μm). In an environment with a relative humidity of 5%, 1,2-dibromoethane was sprayed and coated on the surface of the lithium metal to form a liquid film with a thickness of 50-1000 μm as an artificial SEI film-forming sacrificial agent. A smooth 2H stainless steel roller was used to perform a rough rolling of the lithium-copper composite strip at an absolute reduction of 8 μm, and then the dibromoethane liquid film was re-coated (the coating thickness was 50-1000 μm). A 4H stainless steel roller was used to perform a finish rolling at an absolute reduction of 1 μm for one pass, thereby obtaining a lithium-copper composite strip with a smooth surface and coated with a bromine-rich artificial SEI, which was named R-LiBr / Li-Cu ( Figure 1 ). Scanning electron microscope analysis shows that the surface of lithium metal is flat, and energy spectrum analysis further proves that a large amount of bromine elements are continuously and evenly distributed on the surface of lithium metal, proving that the solution of the present invention can effectively optimize the surface quality of lithium-copper composite strips ( Figure 2 ).
[0043] As a control, in an environment with 5% humidity, polyethylene was used as a release film to coat the lithium metal surface of the lithium-copper composite tape, and the 80μm thick lithium-copper composite tape (lithium metal thickness is 70μm) was subjected to unlubricated cold rolling using the same rolling process. After rolling, the lithium-copper composite tape was still coated with a dibromoethane liquid film (thickness is 200μm) as a film-forming sacrificial agent by spraying and scraping. Under the protection of an argon atmosphere, it was heat treated at 45°C for 24h to achieve surface artificial SEI film formation, and a heat-treated film-forming bromine-rich artificial SEI-coated lithium-copper composite tape control group H-LiBr / Li-Cu was obtained. Scanning electron microscopy observations revealed that the heat-treated film had obvious microcracks, proving that it is difficult to achieve continuous artificial SEI coating by heat-treated formation processes. In subsequent energy spectrum characterization, the bromine element on the surface of H-LiBr / Li-Cu was unevenly distributed, proving that it is difficult to achieve continuous and uniform SEI by traditional formation processes ( Figure 3 ).
[0044] Example 2 The R-LiBr / Li-Cu and H-LiBr / Li-Cu prepared in Example 1 were punched and cut into discs with a diameter of 16 mm, and then matched with 80 μL of 1M LiPF6 / EC+DEC ester electrolyte, and symmetric half-cells were assembled with Celgard2400PP membrane and CR2032. 2 The charge and discharge current density and charge and discharge time of 2h were repeated for charge and discharge tests, while the control group H-LiBr / Li-Cu was 1mA / cm 2The charge and discharge current density and charge and discharge time of 1h were used for repeated charge and discharge tests. After multiple cycles, the R-LiBr / Li-Cu half-cell in the experimental group maintained a flat voltage curve ( Figure 4 ), while the control group H-LiBr / Li-Cu could not achieve stable charge-discharge cycles ( Figure 5 ).
[0045] Example 3 In order to explore the reasons for the difference in cycle performance of bromine-rich SEI-coated lithium-copper negative electrodes prepared by different processes, the R-LiBr / Li-Cu and H-LiBr / Li-Cu electrode samples of the two groups of batteries in Example 2 were taken out respectively, and their surface morphologies were observed using a scanning electron microscope. According to the surface morphology of the samples, the R-LiBr / Li-Cu electrode maintained a relatively flat morphology in the ester electrolyte system, while the surface of the H-LiBr / Li-Cu electrode was severely cracked and powdered, proving the effect of the simultaneous flattening of the lithium metal surface and artificial SEI coating of the lithium-containing metal belt of the present invention on the surface quality of the lithium metal and the optimization of the artificial SEI ( Figure 6 ).
[0046] Example 4 In order to further verify the electrochemical performance of the lithium-copper composite tape prepared by the design scheme of the present invention, R-LiBr / Li-Cu and H-LiBr / Li-Cu were used as negative electrode materials, respectively, and commercial lithium iron phosphate (LFP, active material surface loading ~19 mg / cm 2 ) as the positive electrode material, 80μL of 1M LiPF6 / EC+DEC as the electrolyte, celgard2400PP membrane and CR2032 assembled the full battery. After 200 cycles, R-LiBr / Li-Cu||LFP showed good coulombic efficiency (99.79±0.06%) and low capacity decay rate (2.52%), and the polarization voltage was stable at 80~110mV; while H-LiBr / Li-Cu||LFP had low coulombic efficiency and poor stability (99.61±0.76%) during 150 charge and discharge cycles, and a high capacity decay rate (7.61%), and its polarization voltage increased rapidly from 80mV to 150mV ( Figure 7-9 ).
[0047] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A simultaneous treatment process for surface flattening and artificial SEI coating of a lithium-containing metal strip, characterized in that: The following steps are involved: S1, pre-coating a film-forming sacrificial agent on the lithium metal surface of the lithium metal strip to form a liquid film; S2: using a flat and smooth metal roller to roll the lithium metal surface of the lithium metal strip, thereby simultaneously achieving lithium metal surface flattening and surface artificial SEI coating; The film-forming sacrificial agent serves as both a rolling lubricant and a sacrificial agent precursor required for the formation of an artificial SEI to react with lithium metal to form an artificial SEI film.
2. The simultaneous treatment process for surface flattening and artificial SEI coating of a lithium-containing metal strip according to claim 1, characterized in that: The film-forming sacrificial agent is selected from at least one of the following substances: liquid halogenated hydrocarbons and their derivatives, inorganic salt solutions, sulfide small molecule solutions; or a mixed solution consisting of one or more of the above substances.
3. The simultaneous treatment process for surface flattening and artificial SEI coating of a lithium-containing metal strip according to claim 2, characterized in that: in, Liquid halogenated hydrocarbons and their derivatives include, but are not limited to, one or more of halogenated alkanes, alkenes, benzene-based organic small molecules and their derivatives such as 1,2-dibromoethane, trichloroethylene, hexafluorobenzene, pentafluorobromobenzene, etc.; The inorganic salt is at least one of nitrates / phosphates, wherein the metal ions of the nitrates and phosphates include but are not limited to silver, zinc, aluminum, tin, germanium, gallium, indium, niobium, antimony, bismuth, and molybdenum; The sulfide small molecules include organic small molecules and inorganic salts, wherein the organic small molecules include at least one of DtbDS, DPDSe, DPDTe, DMDS, DMTS, AMDS, BTB, and ADS, and the inorganic salts include one or more sulfides or polysulfides of lithium, silver, zinc, aluminum, tin, germanium, gallium, indium, niobium, antimony, bismuth, and molybdenum metals.
4. The simultaneous treatment process for surface flattening and artificial SEI coating of a lithium-containing metal strip according to claim 1, characterized in that: The lithium-containing metal belt is selected from any one of a pure lithium metal belt, a binary or multinary alloy belt of lithium and any other metal, a lithium-copper composite belt, and a lithium-carbon composite belt.
5. The simultaneous treatment process for surface flattening and artificial SEI coating of a lithium-containing metal strip according to claim 4, characterized in that: The metallic lithium or lithium alloy is distributed on at least one side of the metal strip. The thickness of the lithium-containing metal strip is 1 to 100 μm, and the lithium content is 1 to 100%.
6. The simultaneous treatment process for surface flattening and artificial SEI coating of a lithium-containing metal strip according to claim 1, characterized in that: The thickness of the liquid film formed in step S1 is 10 to 100 μm.
7. The simultaneous treatment process for surface flattening and artificial SEI coating of a lithium-containing metal strip according to claim 1, characterized in that: In step S2, the rolling process conditions are: processing stress is 1-100Mpa, single rolling reduction is 0.01-1mm, roller linear speed is 0.1-100cm / s, the processing process is a combination of rough rolling and finish rolling, and the rolling passes are 2-10 times.
8. The simultaneous treatment process for surface flattening and artificial SEI coating of a lithium-containing metal strip according to claim 1, characterized in that: The following steps are involved: S1, pre-coating 1,2-dibromoethane as a film-forming sacrificial agent on the lithium metal surface of the lithium-copper composite strip to form a liquid film; S2: Use a flat and smooth metal roller to roll the lithium metal surface of the lithium metal strip, and simultaneously achieve lithium metal surface flattening and surface artificial SEI coating. The rolling process conditions are: The relative humidity of the processing environment is 5-10%, the rolling passes are 2-5 times, the rolling process is 2H rough rolling followed by 4H finishing rolling, the single rough rolling reduction is 1-10μm, the single finishing rolling reduction is 0.1-2μm, the roll winding speed is 1-30cm / s, and the relative humidity of the rolling processing environment is 5-10%.
9. A modified lithium-containing metal belt, characterized in that: It is prepared by the method according to any one of claims 1 to 8.
10. Use of the modified lithium-containing metal strip as claimed in claim 9 as a negative electrode material in a lithium metal primary / secondary battery.
Citation Information
Patent Citations
Preparation method of metallic lithium strip and metallic lithium strip prepared by the same
CN104993094A
Preparation method of lithium metal negative electrode, lithium metal negative electrode and lithium metal battery
CN117673273A
Manufacture of lithium metal foil or lithium alloy foil
JP1998058007A
Method of rolling lithium foil
JP2018126780A
Ultra-thin lithium film laminate and method for preparing the same
US20240204262A1